ADMINISTRATIVE AND LEGAL MEASURES OF COUNTERACTION OF CORRUPTION AND CORRUPTION RISKS IN PUBLIC AUTHORITIES - Мельник, Олег Олександрович; Данченко, Роман Олегович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article deals with the possibility of emergence and detection of corruption manifestations and actions during the performance of their duties by officials of state authorities. Methods of research: used methods of analysis, comparison and synthesis. Results: a number of measures are proposed to improve the counteraction to corruption in public authorities.